Analysis of Springback in Rotary Draw Bending Process: Numerical Modelling with Experimental Validation - Amaral Rui L.; Cruz Daniel J.; Almeida Maria; Barros Manuel; Santos Abel D.; Reis Ana (MATEC Web of Conferences)
Tubular components are widely used in aerospace and automotive industries due to their high strength, rigidity, energy absorption and light weight. Among tube bending techniques, Rotary Draw Bending (RDB) is the most industrially adopted due to its precision and versatility. However, elastic recovery after forming affects dimensional accuracy and must be carefully controlled. This phenomenon modifies the bent tube's angle and radius, impacting final part quality. This study models the RDB process using a simplified FEM to analyze key parameters, including bending angle, centerline radius, material thickness and their effect on elastic recovery. The model was validated through experiments with different testing parameters. Results demonstrated that an increase in bending angle doesn't significantly impact the elastic recovery radius but leads to an increase in the elastic recovery angle. Furthermore, an increase in the bend die radius leads to an increase in the elastic recovery radius and a decrease in the elastic recovery angle. The tube thickness doesn't significantly affect the elastic recovery radius or the elastic recovery angle for the studied material. Based on these findings, a predictive model was developed to support the design of industrial bending machines by correlating process variables with the tube geometry after elastic recovery.